2017
DOI: 10.1371/journal.pone.0182340
|View full text |Cite
|
Sign up to set email alerts
|

Detailing neuroanatomical development in late childhood and early adolescence using NODDI

Abstract: Diffusion tensor imaging (DTI) studies have provided much evidence of white and subcortical gray matter changes during late childhood and early adolescence that suggest increasing myelination, axon density, and/or fiber coherence. Neurite orientation dispersion and density imaging (NODDI) can be used to further characterize development in white and subcortical grey matter regions in the brain by improving specificity of the MRI signal compared to conventional DTI. We used measures from NODDI and DTI to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
115
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(142 citation statements)
references
References 33 publications
(48 reference statements)
22
115
5
Order By: Relevance
“…NODDI measures help to clarify trends in DTI measures, and have been leveraged by previous cross‐sectional studies to describe age‐related trends in white matter with greater specificity. Our longitudinal results are in line with previous cross‐sectional findings of positive correlations between NDI and age and no correlation with ODI during adolescence (Chang et al, ; Genc, Malpas, et al, ; Mah et al, ). While most regions and measures showed linear trends, quadratic models outperformed linear models for MD in the splenium, and NDI in all regions except the right IFOF, right CST, and splenium, however, quadratic age effects did not survive multiple comparisons.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…NODDI measures help to clarify trends in DTI measures, and have been leveraged by previous cross‐sectional studies to describe age‐related trends in white matter with greater specificity. Our longitudinal results are in line with previous cross‐sectional findings of positive correlations between NDI and age and no correlation with ODI during adolescence (Chang et al, ; Genc, Malpas, et al, ; Mah et al, ). While most regions and measures showed linear trends, quadratic models outperformed linear models for MD in the splenium, and NDI in all regions except the right IFOF, right CST, and splenium, however, quadratic age effects did not survive multiple comparisons.…”
Section: Discussionsupporting
confidence: 93%
“…While some of these measures have been applied in studies of white matter development, major knowledge gaps remain unexplored. Cross‐sectional studies have applied NODDI to show NDI is more sensitive to age‐related change than FA or MD (Genc, Malpas, Holland, Beare, & Silk, ), and increases during late childhood and adolescence (Chang et al, ; Genc, Malpas, et al, ; Mah, Geeraert, & Lebel, ). On the other hand, ODI undergoes little to no change during childhood and adolescence, suggesting fiber coherence is established early and remains stable during childhood.…”
Section: Introductionmentioning
confidence: 99%
“…164 Another NODDI study of 27 children aged 8-13 years showed positive NDI-age correlations in all tracts, and no ODI-age correlations. 81 Together, these suggest increasing myelin and/or axonal packing, but negligible changes in axon coherence during development. Finally, a NODDI study of 72 children and adolescents aged 4-19 years demonstrated that NDI is more strongly correlated with age than FA in healthy adolescents, suggesting that it is a better measure of age-related change.…”
Section: Advanced Diffusion Modelsmentioning
confidence: 96%
“…A NODDI study in 66 healthy subjects from 7 to 63 years showed a logarithmic growth pattern of neurite density index (NDI) and an exponential growth pattern of the neurite orientation dispersion index (ODI); between 7 and 20 years, the ODI was flat, whereas NDI increased, coinciding with known increases of FA . Another NODDI study of 27 children aged 8–13 years showed positive NDI‐age correlations in all tracts, and no ODI‐age correlations . Together, these suggest increasing myelin and/or axonal packing, but negligible changes in axon coherence during development.…”
Section: Advanced Techniques May Provide Further Insightmentioning
confidence: 99%
“…Studies utilizing FBA in a neurodevelopmental context suggest white matter development from late childhood to early adulthood may be driven by increases in both axonal packing/density and fiber bundle size (Genc et al, 2017b(Genc et al, , 2018b(Genc et al, , 2018a(Genc et al, , 2019. Age-related increases in axonal packing/density from late childhood to adulthood have also been suggested by studies utilizing an alternative diffusion model, "neurite orientation and dispersion density imaging (NODDI)" (Chang et al, 2015;Genc et al, 2017a;Mah et al, 2017); these changes have been shown to occur alongside increasing FA and decreasing MD during late childhood to adulthood and correlate more strongly with age than DTI metrics (Genc et al, 2017a;Mah et al, 2017). Taken together, these findings suggest that increasing axonal density/packing and fiber bundle size underlie the DTI changes observed in late-childhood to adulthood, though whether this is the case in early childhood remains unclear.…”
Section: Introductionmentioning
confidence: 99%